2007
DOI: 10.5688/aj710228
|View full text |Cite
|
Sign up to set email alerts
|

Using the Humanities to Strengthen the Concept of Professionalism Among First-professional Year Pharmacy Students

Abstract: Objectives. To engage pharmacy students at the McWhorter School of Pharmacy in an authentic discussion of professionalism early in their education. Methods. A booklet was prepared that included several classic short stories and essays that dealt with professionalism. This booklet was sent to all entering students in the class of 2008 and 2009 during the summer prior to their first-professional year of the PharmD program. The stories and essays were discussed in small groups with faculty facilitation during ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…The School of Pharmacy at Samford University has incorporated a unique program into new student orientation, in which great works of literature are used to impress upon students the moral dimension of being ''called to serve,'' which the authors suggest to be the core element of professionalism. 28 Culture change can also be accomplished by faculty members being vigilant to identify unprofessional influences and to vigorously defend professional values with ''counter-detailing.'' Students need constant reassurance from counter-arguments to offset negative influences.…”
Section: Fostering Professionalismmentioning
confidence: 99%
“…The School of Pharmacy at Samford University has incorporated a unique program into new student orientation, in which great works of literature are used to impress upon students the moral dimension of being ''called to serve,'' which the authors suggest to be the core element of professionalism. 28 Culture change can also be accomplished by faculty members being vigilant to identify unprofessional influences and to vigorously defend professional values with ''counter-detailing.'' Students need constant reassurance from counter-arguments to offset negative influences.…”
Section: Fostering Professionalismmentioning
confidence: 99%
“…McWhorter School of Pharmacy at Samford University used a collection of short stories to enforce concepts related to professionalism. 9 Assessment survey instruments designed to measure the impact of these readings on perceptions among incoming students indicated that the reading assignments were a positive influence on this cohort compared with prepharmacy students who had not read the stories. 9 At the Eshelman School of Pharmacy at the University of North Carolina, also uses a common reading experience, a facilitated book discussion is held during orientation for first-year students to explore concepts related to the…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication described a professionalism program that requires newly admitted pharmacy students to read four short stories that focus on professionalism during the summer prior to their first professional year. When the students first arrive on campus for orientation, they are divided into small groups and with the direction of faculty members, they discuss the readings and their relevance to the practice of pharmacy (Bumgarner, 2007). Faculty members found that this program helped the newly admitted students in fostering professional attitudes and behaviors (Bumgarner, 2007).…”
Section: Responsibilities Of the Educatormentioning
confidence: 99%
“…When the students first arrive on campus for orientation, they are divided into small groups and with the direction of faculty members, they discuss the readings and their relevance to the practice of pharmacy (Bumgarner, 2007). Faculty members found that this program helped the newly admitted students in fostering professional attitudes and behaviors (Bumgarner, 2007). During these early years, when students are obtaining "textbook knowledge," they should also begin to inculcate the tenets of professionalism including: excellence, accountability, duty, honor and integrity.…”
Section: Responsibilities Of the Educatormentioning
confidence: 99%